Waste diversion through composting its applicability to the city of Calapan and implication to the local economy - Benter, Amormio Joseph Andrew S. (2006)
The study aims to help reduce the wastes generated in the City of Calapan through composting. Existing national laws and local ordinances related to solid waste management were reveiwed. Interviews with local officials were conducted to determine the current practices and future programs of the City Government of Calapan (CGC). A survey participated by 115 respondents from 31 barangays was also done to determine their level of awareness and participation to the CGC's program. The survey showed that the common practice in waste management in the service area was through collection of wastes by trucks. Their perception about composting process was about converting waste into fertilizer. They had little knowledge about RA 9003 or the Ecological Solid Waste management Act of 2000. However, the respondents were aware of the existence of local ordinance on solid waste management. They were also satisfied with the solid waste management services offered by the CGC in terms of personnel and equipment. They also willing to segregate and compost their waste if given proper information and training. However, they were uncertain about the suitability and effectiveness of CGC's solid waste management program but they were willing to support the local government. Waste analysis Characterization Study (WACS) was also undertaken. It showed that food and kitchen wastes were prevalent both in Batino dumpsite and public market. The present solid waste generation of the service area is 30 tons per day which translates to 0.44k/person per day. A total of 23.40 tons of waste could be composted daily. The establishment of a composting facility shall provide significant contributions in abating the serious problems of poor solid waste management. This will require a large amount of capital expenditure to finance the cost of infrastructure, equipment, materials, manpower, and training for its operation and maintenance. this investment can be recovered within four years provided that a good marketing strategy is implemented by the CGC. The strict enforcement of the law and local ordinances by the concerned authorities including the active participation of the local residents, government agencies, and private sector will lead to a successful establishment of a composting facility which in turn will contribute to effective solid waste management in CGC.